Manhaj taʿlīm al-lughah al-ʿArabiyyah bi-Kitāb al-ʿArabiyyah Bayna Yaday Awlādina fī al-Madrasah al-Rāyah al-Ibtidāʾiyyah Sukabumi - Solihati, Septia; Hasanah, Mamluatul; Ma'ali, Abul (Kalamuna: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2023)
The key to effective education lies in a well-structured curriculum comprising learning objectives, content, methods, and assessment. This study aims to (1) describe the implementation of the Arabic language curriculum for fifth-grade students at SD Ar-Raayah Sukabumi School and (2) identify the factors hindering Arabic language learning among these students. The research was conducted using a qualitative approach, employing various qualitative methods. The participants in this study were elementary students from Banner Sukabumi. The research findings revealed that the objectives of teaching Arabic at Ar-Raayah Primary School encompassed vocabulary acquisition and its practical application, dialogue memorization, and comprehension of vocabulary, as well as proficiency in reading, speaking, and writing. The assessment methods used in this curriculum included continuous evaluation through training, midterm evaluations, and final exams. In conclusion, the formulation of educational objectives and content selection for the Arabic language curriculum were designed based on appropriate pedagogical resources and methods that align with students' abilities. The study emphasizes the crucial role of teachers in ensuring a successful education process.